EFFECTS OF ORGANIZATIONAL SUPPORT, SUPERVISOR SUPPORT AND COWORKERS’ INTERPERSONAL HELPING BEHAVIOR ON EMPLOYEE JOB SATISFACTION: A CASE STUDY IN BANGKOK, THAILAND - Pandey, Arti; Chairungruang, Saifon (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Employees’ job satisfaction would lead to more productive working environment in organizations. This study aims to examine the effects of employee’s perception of organizational and supervisor supports as well as coworkers’ interpersonal helping behavior on job satisfaction. The survey is collected data from a total of 50 employees, who works in both private and public organizations in Bangkok, Thailand. The findings show that perceived organizational support, perceived supervisor support and coworkers’ interpersonal helping behavior have positive relationship with employee’s job satisfaction. The suggestions are that, the organizations should keep the employees’ satisfaction level by giving more feedback and reaction on their work apart from organizational support from supervisors. The supervisors also need to coach and help the subordinates in order to achieve their performance. The coworkers also play important role to their coworkers because good coworkers can create a good working environment. The coworkers need to help the coworkers who are still new in their roles, as well as can help when their coworkers suffer from job stress. Organizations should also inform all supervisors to support, coach and giving feedback on their subordinates’ work in order to reduce their job stress and increase job satisfaction.